Association between parity and markers of inflammation: The multi-ethnic study of atherosclerosis - Ezeigwe, Angelica; Ogunmoroti, Oluseye; Minhas, Anum S.; Rodriguez, Carla P.; Kazzi, Brigitte; Fashanu, Oluwaseun E.; Osibogun, Olatokunbo; Kovell, Lara C.; Harrington, Colleen M.; Michos, Erin D. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Multiparity has been associated with increased risk of cardiovascular disease (CVD). Inflammation may be a mechanism linking parity to CVD. We investigated the association between parity and later-life markers of inflammation. Methods We studied 3,454 female MESA participants aged 45–84, free of CVD, who had data on parity and inflammatory markers. Parity was categorized as 0 (reference), 1–2, 3–4, or ≥5. Linear regression was used to evaluate the association between parity and natural log-transformed levels of fibrinogen, D-dimer, GlycA, high sensitivity C-reactive protein (hsCRP), and interleukin-6 (IL-6). Results Mean age was 62 ± 10 years. The proportion of women with nulliparity, 1–2, 3–4, and ≥5 live births were 18, 39, 29, and 14%, respectively. There was no association between parity and fibrinogen. Women with grand multiparity (≥5 live births) had 28, 10, and 18% higher levels of hsCRP, IL-6 and D-dimer, respectively, compared to nulliparous women, after adjustment for demographic factors. After additional adjustment for CVD risk factors, women with 1–2 and 3–4 live births had higher hsCRP and women with 1–2 live births had higher GlycA. Conclusion In this diverse cohort of middle-to-older aged women, we found that higher parity was associated with some inflammatory markers; however, these associations were largely attenuated after adjustment for CVD risk factors. There was no clear dose-response relationship between parity and these inflammatory markers. Future studies are needed to evaluate how inflammation may influence the link between parity and CVD and whether healthy lifestyle/pharmacotherapies targeting inflammation can reduce CVD risk among multiparous women. Clinical trial registration The MESA cohort design is registered at clinicaltrials.gov as follows: https://clinicaltrials.gov/ct2/show/NCT00005487.